GAMBARAN USIA MENARCHE PADA SISWI KELAS VII DAN VIII DI SMP NEGERI 1 KEMBARAN KECAMATAN KEMBARAN PERIODE JULI 2008 - Hidayah Hidayah; Reni Dwi Setyaningsih; Ikit Netra Wirakhmi (Viva Medika, 2009)
Background: Early functioning of the ovary is marked with the first menstruation.Symptoms of menstruation or menstruation is a very important event in puberty as abiomarker of sexual maturation in girls. Menstrual events that occur periodically willcause various reactions of teenagers puberty. Knowledge of reproduction is an importantcapital to undergo a phase of his life and carry out the development process. It is necessaryto avoid potential interference with reproductive health Objective: To determine the age of menarche picture in class VII and VIII in SMP Negeri 1Kembaran period July 2008 Methods: This type of research used in this research is descriptive quantitative researchwith cross sectional approach. Samples were taken by simple random sampling techniquewith a total sample of 73 people. RESULTS: Adolescent girls experience menarche at age ≥ 12 years more that 59respondents (80.8%), the majority of respondents had experienced menarche is not thesame as the biological mother as much as 45 respondents (61.6%), the majority ofrespondents still have a father as many as 59 respondents as many as 56 respondents(94.9%) had menarche at age ≥ 12 years, adolescent girls who experience menarche ≥ 12years on socioeconomic status were as many as 52 respondents (71.3%) Conclusion: Of the 73 respondents, showed more girls experience menarche at age ≥ 12years, the majority of respondents experienced menarche is not the same as the biologicalmother, the majority of respondents still have a father experienced menarche at age ≥ 12years, adolescent girls who experience menarche ≥ 12 years at the most in socio-economicstatus was Keywords : girls, menarche